MULTICULTURAL BASED ISLAMIC EDUCATION IN GROWING THE SPIRIT OF DIVERSITY IN STUDENTS - Anwar, Rosyida Nurul (Proceeding of International Conference on Islamic Education (ICIED), 2022)
The diversity that exists in Indonesia must be arranged harmoniously to avoid friction between cultures, races, ethnicities, and even religions. Islamic religious education has a critical mission to build Muslim characters who understand the teachings of their religion and have faith awareness manifested in daily attitudes and behavior as a form of practicing religious teachings. This study aimed to determine the learning of multicultural-based Islamic religious education in fostering the spirit of diversity in students. The research location is in Junior High School in Mojokerto, East Java. The approach used is descriptive qualitative. Research informants are principals, teachers, students, parents, and all other school members—data collection techniques using interviews, observation, and documentation. Data analysis is data reduction, data display, and conclusion /verification. Research shows that multicultural-based Islamic education fosters the spirit of diversity in students, namely: first, there is a policy of accepting new students who have different ethnic, religious, and racial backgrounds; second, the implementation of learning by upholding the value of mutual respect, love and resolution of conflict and violence; third, realizing tolerance by fostering the spirit of nationalism; the four learning processes that describe the school climate with a multicultural orientation.